2015
DOI: 10.1007/s10900-015-0026-0
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Health Risks for Children Living Near a Major Railyard

Abstract: Inland southern California is a region of public health concern, especially for children, given the area’s perennially poor air quality and increasing sources of local pollution. One elementary school specifically is located only a few hundred yards from the San Bernardino Railyard, one of the busiest goods movement facilities in California, potentially increasing respiratory problems. Through ENRRICH (Environmental Railyard Research Impacting Community Health) Project, we assessed association of proximity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
1
10
0
1
Order By: Relevance
“…The recently implemented California Assembly Bill 617 was designed partially to address disproportionate impacts of air pollution in environmental justice communities, and San Bernardino was selected as a Phase 1 community in 2018 (Garcia, 2017). Previous studies have highlighted health disparities in the San Bernardino community due to its proximity to a large railyard (Spencer-Hwang et al, 2015, 2016. Through our study, we sought to understand personal exposure patterns as they relate to the unique environmental and socioeconomic characteristics of inland Southern California.…”
Section: Study Areamentioning
confidence: 99%
“…The recently implemented California Assembly Bill 617 was designed partially to address disproportionate impacts of air pollution in environmental justice communities, and San Bernardino was selected as a Phase 1 community in 2018 (Garcia, 2017). Previous studies have highlighted health disparities in the San Bernardino community due to its proximity to a large railyard (Spencer-Hwang et al, 2015, 2016. Through our study, we sought to understand personal exposure patterns as they relate to the unique environmental and socioeconomic characteristics of inland Southern California.…”
Section: Study Areamentioning
confidence: 99%
“…A growing body of evidence indicates that traffic emissions and diesel exhaust are associated with increased risk of adverse respiratory health outcomes in children, such as reduced lung function, airway inflammation, wheezing-sounding breathing, coughing, exacerbation of asthmatic symptoms, development of asthma, increased medication use, ER treatment and hospitalizations ( Kim et al, 2004 ; Gauderman et al, 2007 ; Holguin et al, 2007 ; McConnell et al, 2010 ). Moreover, recent evidence has pointed to the additional role of railyard related emissions, impacting children already affected by background pollution ( Spencer-Hwang et al, 2015 ). Our study set out to investigate if our findings from the San Bernardino railyard study were similar to findings observed for freight railyards in general.…”
Section: Discussionmentioning
confidence: 99%
“…While all residents experience the pollution from these sources, young children living in close proximity are at greater risk of developing respiratory health problems. Previous research has identified increased likelihood of adverse respiratory health outcomes of children living and attending school near a major freight railyard ( Spencer-Hwang et al, 2015 ). However, with only limited research assessing impact of freight railyards on the health of children residing in close proximity, there is an urgent need to better understand the potential adverse health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that minority students, particularly Latino students, are more likely to face elevated exposure to air toxins near their school districts (Morello-Frosch, Pastor, and Sadd 2002; Pastor, Morello-Frosch, and Sadd 2006; Pastor, Sadd, and Morello-Frosch 2002). Research has also found that Hispanic children face an increased risk of asthma (Akinbami et al 2012) and other respiratory problems (Spencer-Hwang et al 2015). There is also evidence that Hispanic children are more likely than non-Hispanic white children to visit an emergency room (Oraka et al 2013).…”
Section: A Critique Of the Literaturementioning
confidence: 99%